Efektivitas Instagram Sebagai Media Promosi Dalam Menarik Minat Mendengar Radio Programa 2 Kota Semarang - Fiqhil Maksum; Flora Meliana Siahaan; George W. Bender (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This study aims to determine the effectiveness of Instagram as a promotional medium in attracting Generation Z’s interest in listening to Programa 2 (Pro 2) of Radio Republik Indonesia (RRI) Semarang. The research is based on the limited number of studies regarding the use of Instagram for promoting radio institutions, even though this platform has proven effective in sectors such as tourism and MSMEs. A descriptive quantitative approach was used, with data collected through closed-ended questionnaires. The results show that Instagram content from the @pro2smg account significantly influences Generation Z’s interest in Semarang. Dimensions such as informational content, visual design, interactivity, and content relevance were all rated in the “agree” category. Statistical testing using SPSS 25 indicated a positive correlation between the Instagram content variable (X) and listening interest (Y). Thus, it can be concluded that Instagram is effective as a promotional medium to attract Generation Z listeners to Pro 2 RRI Semarang broadcasts. The findings of this study demonstrate that the Instagram account @pro2smg has a significant effect on the audience’s interest in listening to the broadcast of Programa 2 RRI Semarang. This is substantiated by a contribution of 52.2%, which suggests that more than half of the variance in listening interest is determined by the exposure to content delivered through social media.